Alternatives to biodiversity offsets for mitigating the effects of urbanization on stream ecosystems. Issue 4 (16th April 2018) - Coker, Myles E.; Bond, Nick R.; Chee, Yung En; Walsh, Christopher J.
Abstract: Globally, offset schemes have emerged in many statutory frameworks relating to development activities, with the aim of balancing biodiversity conservation and development. Although the theory and use of biodiversity offsets in terrestrial environments is broadly documented, little attention has been paid to offsets in stream ecosystems. Here we examine the application of offset schemes to stream ecosystems and explore whether they suffer similar shortcomings to those of offset schemes focused on terrestrial biodiversity. To challenge the applicability of offsets further, we discuss typical trajectories of urban expansion and their cascading physical, chemical and biological impacts on stream ecosystems. We argue that the highly connected nature of stream ecosystems and urban drainage networks can transfer impacts of urbanization across wide areas, complicating the notion of like‐for‐like exchange and the prospect of effectively mitigating biodiversity loss. Instead, we identify in‐catchment options for stormwater control, which can avoid or minimize the impacts of development on downstream ecosystems, while presenting additional public and private benefits. We describe the underlying principles of these alternatives, some of the challenges associated with their uptake, and policy initiatives being trialed to facilitate adoption. In conclusion, we argue that stronger policies to avoid and minimize the impacts of urbanization provide better prospects for protecting downstream ecosystems, and can additionally, stimulate economic opportunities and improve urban liveability. Abstract : Article impact statement : Biodiversity offsets poorly compensate for the impact of urbanization on streams.